Review on SLAM of Mobile Robot for Processing Inspection Based on Multi-Sensor Fusion - Ye, Chenghuang; Huang, Ruiyou; Zheng, Xiubao; Feng, Xiaoyu; Zhang, Zhangyu (International Journal of Mechanical and Electrical Engineering, 2026)
With the rapid advancement of Industry 4.0 and smart manufacturing, traditional fixed processing and inspection equipment can no longer meet the flexible manufacturing demands of large-scale and complex-shaped components. Mobile processing and inspection robots, with their high adaptability and efficiency, have become critical equipment in modern workshops. This paper focuses on analyzing two mainstream solutions—visual-inertial fusion (VI-SLAM) and laser-visual fusion—emphasizing the advantages of multi-sensor fusion in enhancing robustness and precision. It provides a detailed exploration of the visual SLAM framework and algorithmic advancements based on feature points and deep learning. Additionally, the study investigates the collaborative design of global path planning and local obstacle avoidance algorithms, aiming to offer technical references for reliable autonomous navigation of mobile robots to preset workpoints in known environments.